Experimental Infection of Mink with SARS-COV-2 Omicron Variant and Subsequent Clinical Disease - Virtanen, Jenni; Aaltonen, Kirsi; Kegler, Kristel; Venkat, Vinaya; Niamsap, Thanakorn; Kareinen, Lauri; Malmgren, Rasmus; Kivelä, Olga; Atanasova, Nina; Österlund, Pamela; Smura, Teemu; Sukura, Antti; et al. (Emerging infectious diseases, 2022)
We report an experimental infection of American mink with SARS-CoV-2 Omicron variant and show that mink remain positive for viral RNA for days, experience clinical signs and histopathologic changes, and transmit the virus to uninfected recipients. Preparedness is crucial to avoid spread among mink and spillover to human populations.